ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO , RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM (STUDY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2014) - Gesti Purnama Sari, 12.05.51.0031; Irsad, Moch. (Students Journal of Economic and Management, 2016)
This research is analize influence current ratio, debt to equity ratio, return on equity, and earning per share to stock price manufacture company listed in BEI 2012-2014. This research is doing because inconsisten the result of previous research. This research was conducted using secondary data from the manufacturing companyâs financial statements, published in 2012-2014. This population in this research are all of the companyâs manufacture listed in BEI 2012-2014. The sampling method in this research is purposive sampling method with sampling judgment sample selection criteria are specified in accordance with the purpose of research .Use the multiple linier regresion analysis, it can be seen that the current ratio of a significant negative effect on stock prices , debt to equity ratio has a significant negative effect on stock prices , return on equity significant positive effect on the stock price and earnings per share positive effect on stock price.Â Keyword : Current Ratio, Debt to Equity Ratio, Return On Equity, Earning Per Share, Stock Price